UMUMTA’LIM MAKTABLARIDA SPORT TADBIRLARINI TASHKIL ETISH - Kuniyazov Х. (SCIENCE and SOCIETY, 2023)
The article presents a detailed analysis of the attitude of students to school sports events, the impact of schoolchildren’s interest in them on the activities of teachers. The conducted studies help to understand the need for further development and implementation of various sports events in the activities of general education schools and all sports organizations. The developed classification of activities is optimally suited for motivating students, both graduates and primary and secondary students, which will significantly increase the coverage of children. Based on the obtained data, the main directions were developed and formulated for organizing events that could attract schoolchildren.